1) 22 2)
Пошаговое объяснение:
1) f `(x)=`=
f `(1)=
2)f `(x)=() ` =3+
f `()=3*+=1/3+9=9
f`(x) = ( + 3x⁷) `= + 21x⁶
f`(1) = + 21 × 1⁶ = 22
f`(x) = (x³ - + 7)` = 3x² +
f`() = 3 × ()²+ =
1) 22 2)![9\frac{1}{3}](/tpl/images/4627/7860/48b54.png)
Пошаговое объяснение:
1) f `(x)=
`=![\frac{1}{\sqrt{x} } +21x^{6}](/tpl/images/4627/7860/633cb.png)
f `(1)=![\frac{1}{\sqrt{1} } +21*1^{6}=22](/tpl/images/4627/7860/fe054.png)
2)f `(x)=(
) ` =3
+![\frac{1}{x^{2} }](/tpl/images/4627/7860/01867.png)
f `(
)=3*
+
=1/3+9=9![\frac{1}{3}](/tpl/images/4627/7860/5506e.png)
f`(x) = (
+ 3x⁷) `=
+ 21x⁶
f`(1) =
+ 21 × 1⁶ = 22
f`(x) = (x³ -
+ 7)` = 3x² + ![\frac{1}{x^{2} }](/tpl/images/4627/7860/16400.png)
f`(
) = 3 × (
)²+
= ![9 + \frac{1}{3} = 9 \frac{1}{3}](/tpl/images/4627/7860/0d02c.png)